High-Frequency Model of Battery in Form of Transfer Function. (26th November 2018) - Cipin, Radoslav; Toman, Marek; Prochazka, Petr; Pazdera, Ivo
Abstract : This paper deals with a measurement of alkaline and Li-ion battery impedances in wide-range frequency from about one Hz to a few hundred kHz. Measured battery admittances are used for the construction of battery transfer functions, i.e., the dependences of admittance on frequency. Comparison of transfer functions for different battery types is shown. It is shown that transfer functions for both types have the same form and this transfer function is only the third-order.